Pemerolehan Sintaksis pada Anak Gifted dengan Speech Delay: Studi Psikolinguistik - Wahyu Agustina; Laila Fitri Nur Hidayah; Kundharu Saddhono (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study aims to analyse language development in gifted children with speech delay, focusing on syntactic acquisition and the factors influencing this process. The subject of this study was an 8-year-old child diagnosed with giftedness and speech delay at an early age. Research data were obtained through triangulation of sources, including observation, interviews with parents and teachers, and documentation of the child’s language development. The results of the study indicate that the child tends to use simple sentences with telegraphic patterns in most of their communication. Complex sentence structures emerged in the context of directed tasks. This suggests that vocabulary acquisition does not always go hand in hand with the ability to construct complex sentence structures. The delay in syntactic acquisition is not caused by low cognitive ability, but rather by difficulties in regulating language production, which results in a predominance of simple sentence structures and limited syntactic patterns. This study also found that social stimulation and interaction with parents, teachers and peers play a major role in accelerating language acquisition. The implications of this research emphasise the importance of an individualised, socially stimulating approach to learning in supporting the syntactic development of gifted children with speech delay.